Implications of thermal stratification and radiative heat flux in blood-based ternary and dihybrid nanomaterial flow through a stretchable cylinder - Muzher Saleem; Ghada A. Khouqeer; Fazal Haq; Naglaa AbdelAll; Arshad Hussain; Mohammed Sallah (Case Studies in Thermal Engineering)
Ternary hybrid nanofluids (THNFs) are advanced thermal fluids that consist of three different types of nanoparticles dispersed in a base fluid. THNFs offer significant advantages in enhanced heat transfer, stability, and customizable properties. Their ability to improve efficiency and reduce energy consumption makes them a valuable option for various industrial and technological applications. The present study addresses the heat transfer performance of magnetohydrodynamic micropolar THNF (TiO2+Al2O3+Ag/blood) and hybrid nanofluid (HNF) (TiO2+Al2O3/blood) flow by vertically stretching cylinder. THNF fluid is developed by suspending the rigid nanoparticles of titanium dioxide (TiO2), aluminum oxide (Al2O3), and silver (Ag) into blood-based micropolar fluid. Phenomenon of thermal stratification is considered at the boundary of the cylinder. Physical aspects of Darcy Forchheimer, magnetic field, and surface porosity are considered in the momentum equation. Energy transport relation is formulated under the influences of heat source, Lorentz force, and internal friction forces. The dimensional flow model is altered into non-dimensional one by implementing the transformations. Non-dimensional mathematical model representing the physical phenomenon is solved through NDSolve function of Mathematica. Behavior of micropolar THNF and HNF velocity and thermal field versus influential variables are investigated. The results are discussed and compared in relation to HNF and THNF. Additionally, variations in Nusselt number, couple stress, and skin friction factors are examined. Heat transfer performance of THNF and HNF are compared via graphs. A reduction of 4 % in the skin friction coefficient of THNF compared to HNF is noticed. The THNF exhibits a higher average percentage heat transfer rate than HNF through variables curvature, Eckert number, Prandtl number, heat source, and thermal stratification, with values of 146, 135, 142, 139, 138, 150, and 140, respectively.